Kombucha tradicional e saborizadas com pitanga (Eugenia uniflora L.) e com umbu-cajá (Spondia tuberosa): caracterização química, compostos voláteis, bioativos e potencial antioxidante - Silva Júnior, Jayme César da (2021)
Kombucha is a fermented tea of Chinese origin that stands out due to the beneficial properties associated with its consumption, such as its antioxidant capacity, anti-inflammatory effect and anti-cancer activity. Given the rise of the drink, studies have been using alternative raw materials for the preparation of analogous kombuchas, such as fruit. In this sense, the main objective of the study was to prepare traditional green tea kombucha (KT) and to evaluate the impacts of the addition of pitanga (KSP) and umbu-cajá (KSUC) pulps in different storage times, in terms of pH, acidity total titratable, soluble solids content, organic acid, sugar, volatile and phenolic acid profiles. Additionally, the in vitro gastrointestinal digestion was evaluated on the bioaccessibility of phenolic compounds and in vitro antioxidant activity in the kombuchas produced. The study also enabled the elaboration of a review article, contributing with relevant information about the kombucha drink. Initially, the green tea KT was made from the infusion of dehydrated leaves at 1.25% (w/v), sugar at 7.5% (w/v), 20% (v/v) of the starter tea and 3 % SCOBY (w/v), maintained at 25°C ± 2°C in BOD incubator. After 7 days of fermentation, the culture was removed, the tea was filtered and fractionated into three portions of the same volume and then 15% (w/v) of the fruit pulps (pitanga and umbu-cajá) were added, followed by the drinks were kept at 25°C (± 2°C) for 48h in BOD. At the end of this step, the drinks were filtered and filled into sterile bottles (5°C ± 2°C). During the period evaluated, all beverages presented reduced pH, increased acidity, decreased soluble solids, and reduced sugars (glucose and fructose). Higher values and lower sugar losses were recorded for flavored beverages, evidencing that pre-existing glucose and fructose contents in fruits contributed to sweeter beverages. Organic acetic, butyric, citric, succinic and malic acids were identified in all kombuchas, with the exception of malic acid in KSP. Terpenes (more than 39% of area) were the main volatile compounds reported in beverages, as they contributed to the increase and/or emergence of new terpenoids, such as curzerene and β-caryophyllene. Fifteen polyphenols were identified in KT and 16 in KSP and KSUC, with the flavonoid gallate epigallocatechin standing out in all kombuchas, with values ranging from 63.69% to 76.84%. However, the most bioaccessible phenolics in all beverages were caffeine (22.38% to 29.98%), catechin (17.61% to 23.48%) and hesperidin (22.43% to 28.47% ). The results of antioxidant activity of beverages showed variations among themselves, and considerable reductions in bioaccessible fractions, between the DPPH and ORAC methods and evaluated times. In the DPPH assay, the addition of pitanga and umbu-cajá pulps resulted in an increase in the antioxidant capacity in PF0 in KSP (2489.41 μM TEAC/100 mL) and in KSUC (2459.05 μM TEAC/100 mL), where these drinks did not show significant differences (p ≤0.05). However, KT (2690.98 μM TEAC/100 mL) had the highest antioxidant capacity at the end of the 7 days of observation. As for the ORAC test, all beverages showed a significant increase (p ≤0.05) at the end of refrigerated storage. Our findings indicate that the use of pitanga and umbu-cajá are interesting alternatives in the preparation of kombucha, both to expand and diversify flavors, but also reflecting on the chemical, bioactive and sensory characteristics of kombucha, revealing a sweeter drink, with a tendency to fruity and floral aromas.